(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article analyzes the widespread prevalence of malaria in the Ferghana region in the late 19th and early 20th centuries and its impact on the social life of the population, the coverage in historical sources and archival documents of the causes of the spread of this disease in the region and its serious social consequences, the issues of establishing medical traditions and medical methods in the fight against malaria. The article also presents conclusions on the specifics and problems of combating malaria.